أثر أنماط اتخاذ القرار لدى القيادات الإدارية بجامعة صنعاء على الأداء الوظيفي للمرؤوسين - الهمداني, عبد الهادي حسين (Journal of Amran University, 2022)
The study aimed to determine the impact of the prevailing decision-making patterns among the administrative leaders at the University of Sana'a. on the job performance of subordinates, as well as determining the relationship between decision-making patterns from the point of view of the leaders themselves, From the point of view of their subordinates, the researcher relied on the descriptive analytical method. The survey lists for measuring the level of job performance of subordinates were applied. On a sample of administrative leaders (general managers), their number reached (30) managers, and among their subordinates (60) employees. The results of the study were: There is a significant impact of the decision-making patterns of administrative leaders at Sana’a University on the job performance of their subordinates. On a sample of administrative leaders (general managers), their number reached (30) managers, and among their subordinates (60) employees. The results of the study were: There is a significant impact of the decision-making patterns of administrative leaders at Sana’a University on the job performance of their subordinates. And that the autocratic and semi-advisory style had a negative impact on the job performance levels of subordinates. And the existence of a significant relationship between the patterns of decision-making from the point of view of the administrative leaders themselves and from the point of view of their subordinates.